High-isolation antenna array using SIW and realized with a graphene layer for sub-terahertz wireless applications - Mohammad Alibakhshikenari (Nature Portfolio, 2021)
Abstract This paper presents the results of a study on developing an effective technique to increase the performance characteristics of antenna arrays for sub-THz integrated circuit applications. This is essential to compensate the limited power available from sub-THz sources. Although conventional array structures can provide a solution to enhance the radiation-gain performance however in the case of small-sized array structures the radiation properties can be adversely affected by mutual coupling that exists between the radiating elements. It is demonstrated here the effectiveness of using SIW technology to suppress surface wave propagations and near field mutual coupling effects. Prototype of 2 × 3 antenna arrays were designed and constructed on a polyimide dielectric substrate with thickness of 125 μm for operation across 0.19–0.20 THz. The dimensions of the array were 20 × 13.5 × 0.125 mm3. Metallization of the antenna was coated with 500 nm layer of Graphene. With the proposed technique the isolation between the radiating elements was improved on average by 22.5 dB compared to a reference array antenna with no SIW isolation. The performance of the array was enhanced by transforming the patch to exhibit metamaterial characteristics. This was achieved by embedding the patch antennas in the array with sub-wavelength slots. Compared to the reference array the metamaterial inspired structure exhibits improvement in isolation, radiation gain and efficiency on average by 28 dB, 6.3 dBi, and 34%, respectively. These results show the viability of proposed approach in developing antenna arrays for application in sub-THz integrated circuits.